Depositional Environment Analysis of Kali Banyumeneng, Mranggen, Kabupaten Demak - Samuel R.N. Simorangkir; Fahmi Abdillah; Zul Hayuddin; Galang Virgiawan (Berita Sedimentologi, 2013)
Kali Banyumeneng is located in Mranggen, Demak (Central Java province). The studied outcrop is located approximately 11.25 km to the SE of Semarang city and at the geographic coordinate of 100° 28’ 59.65” E and 7° 02’ 43.45” S.The study area is geologically located in Kendeng Zone, which is also often referred as Kendeng Mountains, an east-west trending anticlinorium in the northern part of Java. The northern border of the Kendeng Zone is Randublatung Depression, while the southern border comprises a line of volcanoes called Solo Zone. Kendeng zone is a continuation of the Northern Mountains Serayu Zone that developed in Central Java. The Salatiga section of the Kendeng zone extends towards the east to Mojokerto and plunges under the Brantas river. The continuation of these mountains can still be tracked under the Madura Strait.Van Bemmelen (1949) subdivided Kendeng Mountains into 3 parts that consist of the western part, which lies between Mt. Ungaran and Solo (north Ngawi); the central part that lies between Solo and Jombang and the eastern part that extends from east Jombang to Brantas River Delta and continuously to Madura Bay. The study area occurs in the western Kendeng Zone. Previous work shows that the study area consists of two lithostratigraphic units called Kerek and Kalibeng Formations. Kerek Formation consists of interbedded sandstones, claystones, and sandy limestones with observed sedimentary structures such as graded bedding, ripple mark and convolute. Kalibeng Formation is subdivided into lower and upper parts. The lower part of Kalibeng Formation consists of sandstones that shows turbiditic nature. The upper part of Kalibeng Formation is composed of breccias with fragments formed by limestone. The Upper Kalibeng Formation also contains forams, molluscs, corals and algae and it shows a bedding structure.Observations were carried out to determine the depositional environment model of Kali Banyumeneng area based on lithology, sedimentary structures and fossils.